1999
DOI: 10.1001/jama.282.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Role of Serology in the Diagnosis of Lyme Disease

Abstract: Numerous concerns regarding the potential for misdiagnosis of Lyme disease using commercial assays have been voiced by the US Food and Drug Administration (FDA). We attempted to clarify the clinical value of serologic testing for Lyme disease using the results of commonly marketed assays for detecting antibody to Borrelia burgdorferi, the organism that causes Lyme disease. We reviewed published studies on B burgdorferi test performance published through 1998, package insert labeling from FDA-cleared test kits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
76
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 23 publications
0
76
0
1
Order By: Relevance
“…Preliminary studies in our laboratory have demonstrated considerable variation in Lyme WB results when strips are visually read by different laboratory technologists (M. Binnicker, unpublished data). This variation in WB results may contribute to inaccurate diagnoses, resulting in various consequences to patients, as described in past studies (4,13,14,17). Therefore, an important need of clinical laboratories is to enhance the objectivity and consistency of Lyme WB interpretation.…”
Section: Discussionmentioning
confidence: 95%
“…Preliminary studies in our laboratory have demonstrated considerable variation in Lyme WB results when strips are visually read by different laboratory technologists (M. Binnicker, unpublished data). This variation in WB results may contribute to inaccurate diagnoses, resulting in various consequences to patients, as described in past studies (4,13,14,17). Therefore, an important need of clinical laboratories is to enhance the objectivity and consistency of Lyme WB interpretation.…”
Section: Discussionmentioning
confidence: 95%
“…When used to assess the first line of antibody response in LB, IgM serology is often prone to specificity problems due to cross-reactive antibodies from other infections (Brown et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…For serologic confirmation of Borrelia burgdorferi infection, a two-step approach with ELISA as a screening test and Western blotting as a confirmatory test is recommended by the Centers for Disease Control (CDC) (Brown et al, 1999). This approach has been challenged not only because it is labour-intensive and time-consuming, but also because the criteria for a positive Western blot vary according to which Borrelia strains are used as antigens and to local variations in the infective species of Borrelia (Robertson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For serodiagnosis, a two-step process, including an enzyme-linked immunosorbent assay (ELISA) followed by Western immunoblot analysis, is recommended in Europe and the United States. Serological tests are widely used despite several shortcomings, such as the heterogeneity of antigen preparations and a lack of standardization causing interlaboratory variation (3,23). Furthermore, serological tests show insensitivity in the early stages of LB (1,13).…”
mentioning
confidence: 99%